Drug interactions between emergency contraceptive drugs and cytochrome inducers: literature review and quantitative prediction. (7th September 2020) - Le Corvaisier, Claire; Capelle, Aude; France, Mathilde; Bourguignon, Laurent; Tod, Michel; Goutelle, Sylvain
Abstract: The emergency contraceptive drugs (EC), levonorgestrel (LNG) and ulipristal acetate (UPA), are sensitive substrates of cytochrome P450 3A4 (CYP3A4). In 2016, the label of LNG was updated based on a drug–drug interaction (DDI) study showing a significant decrease in LNG exposure when co‐administered with efavirenz, a known CYP3A4 inducer. DDI between UPA and CYP3A4 inducers are poorly characterized. The aims of this study were to review quantitative data from the literature on DDI with EC, to provide quantitative predictions of DDI between UPA and CYP3A4 inducers, and to identify moderate and severe DDI that may require a dose adjustment. A literature search was performed on pharmacokinetic DDI of LNG and UPA. Quantitative prediction of DDI with UPA was carried out by using the in vivo mechanistic static model (IMSM). Limited information was available on DDI with emergency contraception drugs. For LNG, data from eleven studies were retrieved, including five known CYP3A4 inducers that confirmed a risk of underexposure to LNG when co‐administered with inducers. For UPA, only three studies were identified, including only one CYP3A4 inducer. The IMSM approach indicated that UPA is a sensitive substrate of CYP3A4, with an estimated contribution of 86% of CYP3A4 to oral clearance. Moderate to severe DDI were predicted in 17 cases with CYP3A4 inducers, and dosage adjustments were suggested. This study illustrates the ability of the IMSM approach to inform about the DDI profile of old and new drugs.